2017
DOI: 10.3122/jabfm.2017.02.160274
|View full text |Cite
|
Sign up to set email alerts
|

Fitwits TM Leads to Improved Parental Recognition of Childhood Obesity and Plans to Encourage Change

Abstract: Introduction: Brief tools are needed to help physicians and parents reach consensus on body mass index (BMI) categories for children and to discuss health-improving behaviors. This study tested the Fitwits TM intervention with interactive flashcards and before and-after surveys to improve parents' perceptions of children's BMI status.Methods: We enrolled 140 parents and their 9-to 12-year-old children presenting for well child care, regardless of BMI status, scheduled with 53 Fitwits-trained physicians. The Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Most quantitative studies were observational (12/14) and used questionnaires , portion size estimation or portioning tasks , a home meal portioning observation or a computer‐assisted interview . Remaining quantitative studies (2/14) were experimental in design but reported data from baseline questionnaires . Qualitative studies used either focus groups or interviews and analysed data using content analysis methods (12/14) or grounded theory .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most quantitative studies were observational (12/14) and used questionnaires , portion size estimation or portioning tasks , a home meal portioning observation or a computer‐assisted interview . Remaining quantitative studies (2/14) were experimental in design but reported data from baseline questionnaires . Qualitative studies used either focus groups or interviews and analysed data using content analysis methods (12/14) or grounded theory .…”
Section: Resultsmentioning
confidence: 99%
“…surveyed parents (79% female) of low to middle socioeconomic status during a routine child health assessment . Seventy‐five per cent reported the portion sizes eaten by their child (aged 9–12 years) as ‘about right’, compared with 23% as ‘too much’ . Most (53%) of children were overweight or obese .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in addition to addressing and recognizing early concerns and assessing the accuracy of parental weight perceptions, delivering these strategies successively over extended periods of time is likely to prove especially successful. In this regard, Edwards et al, 40 found the Fitwits TM intervention with interactive flashcards and before and-after surveys to significantly improve the accuracy of parents' perceptions of their children's body mass status.…”
Section: Discussionmentioning
confidence: 99%
“…Given the extent of our childhood obesity problem, it is wonderful to see a relatively simple, straightforward intervention 7 that helps parents understand their child's level of obesity and changes behavior. For more background information, see also previous JABFM articles about Fitwits 8,9…”
Section: Tmmentioning
confidence: 99%